What Are the Liability Issues in AI-Assisted Surgery? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is rapidly transforming the landscape of medicine, with surgery being one of the most promising frontiers. AI-assisted surgical ...
Keywords: AI in Surgery and Robotics; Liability; Issues; AI-Assisted; Artificial Intelligence; Healthcare